2015
DOI: 10.1038/nm.3979
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of metastasis revealed by mutational landscapes of chemically induced skin cancers

Abstract: Human tumors show a high level of genetic heterogeneity, but the processes that influence the timing and route of metastatic dissemination of the subclones are unknown. Here we have used whole-exome sequencing of 103 matched benign, malignant and metastatic skin tumors from genetically heterogeneous mice to demonstrate that most metastases disseminate synchronously from the primary tumor, supporting parallel rather than linear evolution as the predominant model of metastasis. Shared mutations between primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 59 publications
9
95
0
1
Order By: Relevance
“…In accordance with this model, recent genomic studies of matched primary tumors and metastases suggest independent evolution (76,77). Interestingly, the study of chemically induced skin tumors and metastases suggest that common mutations have an A-to-T signature indicative of the carcinogen while nonshared mutations are G-to-T transitions that signify exposure to oxidative stress (76). Accumulating evidence suggests that disseminating cancer cells undergo profound metabolic reprogramming during the discrete steps to successfully metastasize.…”
Section: Metabolic Plasticity During Metastasismentioning
confidence: 75%
See 1 more Smart Citation
“…In accordance with this model, recent genomic studies of matched primary tumors and metastases suggest independent evolution (76,77). Interestingly, the study of chemically induced skin tumors and metastases suggest that common mutations have an A-to-T signature indicative of the carcinogen while nonshared mutations are G-to-T transitions that signify exposure to oxidative stress (76). Accumulating evidence suggests that disseminating cancer cells undergo profound metabolic reprogramming during the discrete steps to successfully metastasize.…”
Section: Metabolic Plasticity During Metastasismentioning
confidence: 75%
“…In contrast, an alternate hypothesis, referred to as the "parallel progression model," has been proposed that argues metastatic dissemination is an early event during tumor progression (74,75). In accordance with this model, recent genomic studies of matched primary tumors and metastases suggest independent evolution (76,77). Interestingly, the study of chemically induced skin tumors and metastases suggest that common mutations have an A-to-T signature indicative of the carcinogen while nonshared mutations are G-to-T transitions that signify exposure to oxidative stress (76).…”
Section: Metabolic Plasticity During Metastasismentioning
confidence: 99%
“…This relieves the selective pressure to maintain the initial genetic lesion, and is therefore not subject to oncogene addiction. Mouse models of skin and pancreatic cancers have similarly shown that CIN drives metastatic progression (Hingorani et al 2005;McCreery et al 2015). In human tumors, increase in CIN has been linked to metastatic progression in prostate cancer, pancreatic cancer, breast cancer, colorectal cancer, and renal cell carcinoma (reviewed in Turajlic and Swanton 2016).…”
Section: Cin Drives Recurrence and Metastasismentioning
confidence: 99%
“…Progression of cancer can be depicted under the hypothesis of tumor evolution models. However, although the branched evolution model has been widely accepted, it is under debate regarding the metastatic routes of cancer cells [3]. Both linear and parallel models are supported by evidence.…”
Section: Original Papermentioning
confidence: 99%